Inventing black women : African American women poets and self-representation, 1877-2000 - Mance, Ajuan Maria (Knoxville : University of Tennessee Press, 2007)
From Book Jacket Insert: Inventing Black Women fills important gaps in our understanding of how African American women poets have resisted those conventional notions of gender and race that limit the visibility of Black female subjects. The first historical and thematic survey of African American women's poetry, this book examines the key developments that have shape the growing body of poems by and about Black women since the end of slavery and reconstruction, as it offers incisive readings of individual works by important poets such as Alice B Neal, Maggie Pogue Johnson, Alice Dunbar Nelson, Sonia Sanchez, Lucille Clifton, and Audre Lorde, as well as many others. Ajuan Maria Mance establishes that the history of African American women's poetry revolves around the struggle of the Black female poet against two marginalizing forces: the widespread association of womanhood with the figure of the middle-class, white female; and the similar association of Blackness with the figure of the African American male. In so doing, she looks closely at the major trends in Black women's poetry during each of four critical moments in African American literary history: the post-Reconstruction era from 1877 to 1910; the Harlem Renaissance of the 1920s; the Black Arts Movement from 1965-1975; and the period from 1975-2000. Inventing Black Women will prove an invaluable resource for scholars and students of American literature, African American studies, and women's studies.
Acknowledgments -- Introduction: Invisible bodies, invisible work: nineteenth-century American womanhood and the pastoral of the American homescape -- 1: Sole and earnest endeavor: African American women's poetry in the late nineteenth century -- 2: Black woman as object and symbol: African American women poets in the Harlem renaissance -- 3: Revolutionary dreams: African American women poets in the black arts movement -- 4: Locating the black female subject: late-twentieth-century African American women poets and the landscape of the body -- Notes -- Bibliography -- Index.
Includes bibliographical references (p. [185]-194) and index.
Keywords: American poetry -- African American authors -- History and criticism; Women and literature -- United States -- History -- 19th century; Women and literature -- United States -- History -- 20th century; African American women -- Intellectual life -- 19th century; African American women -- Intellectual life -- 20th century; American poetry -- Women authors -- History and criticism; African American women in literature; African Americans in literature; Race relations in literature; Gender identity in literature; Geschichte 1877-2000.; Frauenlyrik -- amerikanische -- Afroamerikanische Autorinnen -- Geschichte 19. Jh; Frauenlyrik -- amerikanische -- Afroamerikanische Autorinnen -- Geschichte 20. Jh; Frauenlyrik; Weibliche Schwarze; Rassenbeziehung -- (Motiv); Geschlechterbeziehung -- (Motiv); American poetry -- African American authors -- History and criticism; Women and literature -- History -- United States -- 19th century; Women and literature -- History -- United States -- 20th century; African American women -- Intellectual life -- 19th century; African American women -- Intellectual life -- 20th century; American poetry -- Women authors -- History and criticism; African American women in literature; African Americans in literature; Race relations in literature; Gender identity in literature; USA